CALCULATION OF LOSS FROM ROUTE UNPRODUCTIVE IDLE VEHICLES IN THE AREA OF STOPPING POINTS IN SCHEDULED PASSENGER TRAFFIC IN GOMEL - , С. А., В. Н. (Municipal economy of cities (Technical science), 2013)
Urban passenger transport is a strategically important sector of the economy of the Republic of Belarus. <span title="От качества транспортного обслуживания населения во многом зависят такие важные показатели, как производительность труда, психофизиологическое состояние пассажиров, а также социальные настроения в целом.">From the quality of public transport services are largely dependent such important factors as productivity, the psychophysiological state of the passengers , as well as social attitudes in general. In this paper, based on previous studies of temporary loss of route vehicles in the area of stopping points Gomel given economic assessment indicated losses.